The Textual Basis of English Translations of the Hebrew Bible - Daley, Stephen. (Supplements to the Textual History of the Bible, 2019)
S. C. Daley's book, The Textual Basis of English Translations of the Hebrew Bible , moves us beyond existing uncertainties about the textual basis of modern Bible translations to a fresh understanding of the text-critical constitution of well-known English translations of the past four hundred years. Most translations depart from the Masoretic Text selectively, and in-depth analysis of their textual decisions leads (1) to the identification of distinct periods in the textual history of the English Bible, (2) to a classification of the translations by eclectic type, and (3) to the observation that each translation is ultimately unique from a text-critical perspective. The study then revisits the topic of the text to be translated in Bibles intended for the wider public.